Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s11739-011-0730-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of gastritis pattern on Helicobacter pylori eradication

Abstract: Helicobacter pylori eradication rate following standard triple therapy is decreasing. Identification of predictive factors of therapy success would be useful for H. pylori management in clinical practice. This study aimed to evaluate the role of different gastritis patterns on the efficacy of the currently suggested 14-day triple therapy regimen. One-hundred and seventeen, consecutive, non-ulcer dyspeptic patients, with H. pylori infection diagnosed at endoscopy, were enrolled. All patients received a 14-day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Our data found that both these triple therapies achieved unsatisfactory eradication rates, with values <80% at ITT analysis. In detail, the cure rate following the standard 14-day triple therapy regimen was consistent to 70-81.7% eradication rates achieved in other Italian studies [5][6][7][8], as well as to 74.8-82.2% observed in other countries, such as Germany, Korea, and Latin America [10,19]. Following the 14-day triple therapy with double-dose PPI we observed a trend towards increased (7-8%) eradication rates when compared to the standard regimen.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our data found that both these triple therapies achieved unsatisfactory eradication rates, with values <80% at ITT analysis. In detail, the cure rate following the standard 14-day triple therapy regimen was consistent to 70-81.7% eradication rates achieved in other Italian studies [5][6][7][8], as well as to 74.8-82.2% observed in other countries, such as Germany, Korea, and Latin America [10,19]. Following the 14-day triple therapy with double-dose PPI we observed a trend towards increased (7-8%) eradication rates when compared to the standard regimen.…”
Section: Discussionsupporting
confidence: 86%
“…The updated Italian guidelines advise a standard 14-day triple therapy for first-line H. pylori eradication [5]. However, following such a therapy, a cure rate less than the auspicated 90% was observed in some trials [6][7][8]. To our knowledge, no study has evaluated the efficacy of a 14-day triple therapy including double-dose PPI in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Current Italian guidelines suggested the use of either 14day triple therapy or 10-day sequential therapy for first-line therapy [3]. However, data of different Italian studies showed that prolonged triple therapy achieved a success rate of only 77% in 619 patients, even when a high-dose proton pump inhibitor was used [4][5][6]. On the contrary, a high success rate was obtained following 10-day sequential therapy in Italy [7], as well as in several other countries [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that the degree of antral inflammation may be more severe and last for longer, resulting in a higher eradication rate in the scarring stage of duodenal ulcer compared to gastric ulcer. In addition, a recent study found that the eradication rate tended to be lower in patients with corpus‐predominant gastritis as compared to those with antral‐predominant gastritis at both intention to treat (ITT) (66.1 vs 74.5%) and per protocol (PP) (80.4 vs 87.2%) analyses, even when a triple therapy is prolonged to 14 days . There might be complex mechanisms involved in the antibiotic distribution in the gastric juice that are affected by gastric mucosal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that affect the eradication rate, such as bacterial resistance to antibiotics [5,8], bacterial density [9,10], cagA status for bacterial factors [11,12], patient compliance [5,13,14], smoking habits [10,15,16], increased body mass index (BMI) [17], diabetes mellitus (DM) [18], polymorphisms of CYP2C19 [19], gastritis pattern [20,21], and type of gastroduodenal disease [22][23][24]. Of those, primary resistance to clarithromycin is the main factor influencing treatment failure; therefore, there have been many strategies to overcome clarithromycin resistance.…”
Section: Introductionmentioning
confidence: 99%